The Determinant Factors Analysis of Entrepreneurial Intentions on University Students Who Are Micro-Small Entrepreneurs - Kusnilawati, Nunik; Suryawardana, Edy; Rianto, Sugeng; Kuswardani, DC; Ariefiantoro, Teguh; Gusmao, Cristino (Jurnal Ilmu Sosial Mamangan, 2025)
Due to the lack of job prospects, micro and small business actors generally start their businesses. Based on theoretical studies, there is a relationship between entrepreneurial ambition, locus of control, personal attitude, ethnicity, and religiosity. Respondents in the research sample numbered 130 people. The tool used was a questionnaire consisting of 26 indicators and five variables. The Likert scale has five possible answers. The location of the study was Semarang. SEM-Amos was used for data processing and analysis. From the initial test, the data were normally distributed and original and reliable. Test the research model for all suitability criteria so that the research model can be accepted. The results of the study based on hypothesis testing showed two things that were not in accordance with the hypothesis: 1). Ethnicity has no real influence on a person's attitude, and 2). Through the mediation of personal attitudes, ethnicity has no real influence on entrepreneurial tendencies. This can be used as a source for further research. Thus, the novelty of this study shows that the variable of entrepreneurial intention is influenced by ethnicity, religiosity, locus of control, and personal attitudes. Then, the implications of research on competency as a mediating variable further strengthen the influence received by the entrepreneurial intention variable from the independent variables (ethnicity, religiosity, locus of control).